A fair AQM scheme for aggregated ECN and non-ECN traffic - Chong, P (2004)
We study the aggregated behaviour of the Transmission Control Protocol (TCP) with and without Explicit Congestion Notification (ECN) over a wide range of traffic conditions using different Active Queue Management (AQM) schemes. A new AQM scheme called Adaptive Rate-Queue Utilisation AQM (ARQUA) which attempts to provide high throughput while maintaining a target delay is proposed. We demonstrate via simulation the aggregated performance advantage of TCP with ECN over TCP without ECN using different versions of TCP in an environment of mixed ECN and non-ECN traffic. We demonstrate that at bottleneck routers, ECN traffic actually degrades the performance of non-ECN traffic when a single marking probability is used to randomly mark and drop the packets. A solution to this problem is proposed: an extension of ARQUA called ARQUA-DAB that dynamically allocates a fair-share bandwidth and queue capacity to each traffic type. (C) 2003 Elsevier B.V. All rights reserved.